Solidarity and universal preparedness for health after covid-19 - Tomson, Göran; Causevic, Sara; Ottersen, Ole Petter; Peterson, Stefan Swartling; Rashid, Sabina; Wanyenze, Rhoda Kitti; Yamin, Alicia Ely (BMJ, 2022)
This article was published in BMJ Global Health by BMJ Journals [This is an Open Access article distributed in accordance with the Creative Commons Attribution Non Commercial (CC BY-NC 4.0) license, Published by BMJ.] and the definite version is available at: https://doi.org/10.1136/bmj.n59 The Journal's website is at: https://www.bmj.com/content/372/bmj.n59